Europium(III)-induced water-soluble nano-aggregates of hyaluronic acid and chitosan: structure and fluorescence. (25th June 2018) - Guo, Junlan; Tang, Jianguo; Wang, Jing; Mao, Sui; Li, Haidong; Wang, Yao; Liu, Jin; Wang, Jing; Wang, Yanxin; Huang, Linjun; Kipper, Matt J.; Belfiore, Laurence A.
Abstract: Abstract : This paper presents new water-soluble bio-polyelectrolyte-based nanoparticles, formed from lanthanide-induced polysaccharide aggregates (LIPAs). These new nano-aggregates are formed by coordinating a photoluminescent lanthanide–ligand complex to a single polyelectrolyte [i.e. polyanionic hyaluronic acid (HA)] or to two oppositely charged polyelectrolytes [i.e. HA and polycationic chitosan (CHI)]. We demonstrate that photoluminescent Eu 3+ –ligand complexes, which are dispersed homogeneously in aqueous solution by the association with water-soluble HA. The polysaccharide supermolecular assembly can be tuned to obtain nanoparticles of different sizes and surface charges. The preparation of stable and water-soluble lanthanide complexes via Eu 3+ –LIPAs opens opportunities for use of luminescent lanthanides in aqueous environments, for biosensing and bioimaging applications.